2017
DOI: 10.1177/0888406417735876
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Practice and Feedback for Developing Teacher Candidate’s Opportunities to Respond Expertise

Abstract: A greater emphasis on measuring the outputs of teacher preparation programs such as practice-based evaluations (e.g., edTPA) has increased the need for teacher educators to examine “best practice” for developing the skill-based competencies of teacher candidates. The purpose of this study was to examine the role of practice and feedback on teacher candidates’ knowledge and skill acquisition of a specific evidence-based practice, the provision of opportunities to respond (OTRs). Using an experimental, pretest–p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Therefore, we discussed the need to increase the amount of structured experiential experiences the preservice teachers engage early in the program to better prepare them for internship and student teaching and provide them opportunities to refine their instructional skills (Janssen et al, 2015). These experiential experiences should be a fundamental and integrated aspect of a special education teacher preparation programs; thus, we need to identify opportunities for deliberate practice throughout the program to help facilitate the development of teaching skills (Sayeski, Hamilton-Jones, Cutler, Earle & Husney, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we discussed the need to increase the amount of structured experiential experiences the preservice teachers engage early in the program to better prepare them for internship and student teaching and provide them opportunities to refine their instructional skills (Janssen et al, 2015). These experiential experiences should be a fundamental and integrated aspect of a special education teacher preparation programs; thus, we need to identify opportunities for deliberate practice throughout the program to help facilitate the development of teaching skills (Sayeski, Hamilton-Jones, Cutler, Earle & Husney, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We encourage teacher educators, as we are doing ourselves, to create experiences that allow preservice special educators to engage with students with disabilities and begin to develop their craft from their first semester in a program. We know that meaningful practice in teaching students can be taught during early coursework in teacher preparation programs (Sayeski et al, 2019) thus, these experiential experiences should be integrated into all courses throughout the program, rather than clustered at the end during practicum and student teaching experiences which is typically the norm. Although special education teacher preparation programs typically note that preservice educators complete several hours in the field before student teaching, the vast majority of these field experiences tend to be observational in nature or unstructured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-eight TESE studies examined the effectiveness of different pedagogical approaches to improving teacher learning (e.g., coaching, video analysis, and multicomponent innovations that include some combination of knowledge development, modeling, practice, and feedback; see Online Appendix A). The vast majority were designed to improve teachers’ knowledge and skill for implementing evidence-based practice (e.g., Kennedy, Rodgers, Romig, Mathews, & Peeples, 2018; Sayeski, Hamilton-Jones, Cutler, Earle, & Husney, 2019). A summary of the research supporting each pedagogical approach follows.…”
Section: Teacher Education Research Since 2010mentioning
confidence: 99%
“…Therefore, performance feedback is an ideal strategy for any teacher who is seeking to improve his or her delivery of academic or behavioral instruction. Performance feedback is effective for teachers during their preservice years (Cornelius & Nagro, 2014; Sayeski, Hamilton-Jones, Cutler, Earle, & Husney, 2017), and it was suggested that performance feedback may be especially helpful for teachers during their induction years as they are beginning to add effective methods to their teaching repertoire (Collins, Sweigart, Landrum, & Cook, 2017). Finally, veteran teachers who are interested in improving specific practices or engaging in new practices may benefit from performance feedback.…”
Section: What Is Performance Feedback?mentioning
confidence: 99%